Reticulate sympatric speciation in Cameroonian crater lake cichlids - Schliewen, Ulrich K (BioMed Central, 2004)
BACKGROUND: Traditionally the rapid origin of megadiverse species flocks of extremely closely related species is explained by the combinatory action of three factors: Disruptive natural selection, disruptive sexual selection and partial isolation by distance. However, recent empirical data and theoretical advances suggest that the diversity of complex species assemblages is based at least partially on the hybridization of numerous ancestral allopatric lineages that formed hybrids upon invasion of new environments. That reticulate speciation within species flocks may occur under sympatric conditions after the primary formation of species has been proposed but not been tested critically. RESULTS: We reconstructed the phylogeny of a complex cichlid species flock confined to the tiny Cameroonian crater lake Barombi Mbo using both mitochondrial and nuclear (AFLP) data. The nuclear phylogeny confirms previous findings which suggested the monophyly and sympatric origin of the flock. However, discordant intra-flock phylogenies reconstructed from mitochondrial and nuclear data suggest strongly that secondary hybridization among lineages that primarily diverged under sympatric conditions had occurred. Using canonical phylogenetic ordination and tree-based tests we infer that hybridization of two ancient lineages resulted in the formation of a new and ecologically highly distinct species, Pungu maclareni. CONCLUSIONS: Our findings show that sympatric hybrid speciation is able to contribute significantly to the evolution of complex species assemblages even without the prior formation of hybrids derived from allopatrically differentiated lineages.